Raputallang sebagai Konsep Konseling Kontekstual di Masyarakat Toraja - Ayub Alexander (Institut Agama Kristen Negeri Toraja, 2019)
The Toraja people understand Raputallang as an expression of personifi-cation (symbolic) in which it expresses the meaning of family relations that are built based on flesh-blood relations (genealogy). The purpose of this research is to explain the concept of Raputallang as a counseling media for the people of Toraja. This research is motivated by the lack of impact and the limited reach of the counseling process carried out by the church to the Toraja people who are facing problems. Therefore, it is necessary to develop counseling media that can reach and provide a more effective impact to help the people of Toraja to improve the value of life which had declined due to the problems they faced. This study, using the theory of Community Counseling, was developed by Judith A. Lewis and colleagues. This paper use a qualitative research with a descriptive approach. The source of this research information are to minaa '(traditional leaders) and cultural observers in Toraja. This research shows that Raputallang becomes or is used as a medium for community counseling through a cultural awareness approach. Abstrak: Masyarakat Toraja memahami Raputallang sebagai ungkapan personifi-kasi (simbolik) yang di dalamnya mengungkapkan makna relasi kekeluargaan yang terbangun berdasarkan hubungan darah daging (genealogi). Tujuan penelitian ini untuk mengkaji Raputallang sebagai media konseling masyarakat Toraja. Penelitian ini dilatar belakangi oleh kurangnya dampak dan terbatasnya jangkauan dari proses konseling yang dilakukan oleh gereja kepada masyarakat Toraja yang sedang menghadapi permasalahan. Oleh sebab itu, perlu dikembangan media kon-seling yang bisa menjangkau dan memberikan dampak yang lebih efektif untuk membantu masyarakat Toraja meningkatkan nilai hidup yang sempat menurun akibat permasalahan yang dihadapinya. Penelitian ini, menggunakan teori Kon-seling Masyarakat yang di Kembangkan oleh Judith A. Lewis dan rekan-rekan. Penelitian kualitatif dengan pendekatan deskriptif. Sumber informasi penelitian ini ialah to minaa’ (tokoh adat) dan pemerhati budaya yang ada di Toraja. Penelitian ini menunjukkan bahwa Raputallang menjadi atau dijadikan sebagai media kon-seling masyarakat melalui pendekatan kesadaran budaya.